2012
DOI: 10.1159/000336054
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Progression of Parkinson’s Disease on Drooling in Various Ethnic Groups

Abstract: Background/Aims: Drooling or sialorrhea is a common non-motor symptom of Parkinson’s disease (PD), and is reported by 35–75% of patients. Drooling is primarily due to impaired swallowing rather than hypersecretion of saliva. In this study, we examined the prevalence of drooling in PD and its relation to various factors such as age, stage of disease, gender and ethnicity. Methods: A retrospective cohort chart analysis of 307 patients with idiopathic PD was conducted. These patients were seen in the Parkinson’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 23 publications
(15 reference statements)
3
18
0
Order By: Relevance
“…In addition, motor severity of PD was observed to be associated with diurnal drooling in the current study, which is consistent with the finding of a case-control study on a Dutch population [6], and another study on a Canadian population [7], which found that all-day drooling was more prevalent with disease progression, especially in H&Y stage 4. However, no association was found between diurnal drooling and disease duration in the current study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, motor severity of PD was observed to be associated with diurnal drooling in the current study, which is consistent with the finding of a case-control study on a Dutch population [6], and another study on a Canadian population [7], which found that all-day drooling was more prevalent with disease progression, especially in H&Y stage 4. However, no association was found between diurnal drooling and disease duration in the current study.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, unlike our previous study on all-day drooling [3], male sex was observed to be associated with diurnal drooling in the current study, which is consistent with a previous Dutch study [6] on diurnal drooling and some studies [7,9,25] on all-day drooling. Why male sex should have severer drooling may be related to the finding that women with PD do seem to have a more benign phenotype than men [26].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies showed that prevalence ranged from 10 to 84% (Table 1) [2,3,4,5,6,7,8,9,10,11,12,13,14,15,16]. Various tools such as the Unified Parkinson's Disease Rating Scale (UPDRS) part II [12,13,14,15]; Scales for Outcomes in PD for Autonomic Symptoms (SCOPA-AUT) [7,16]; PD non-motor symptoms questionnaire (PDNMSQuest) [8,10]; and different types of screening questionnaires [2,3,4,5,6,7,10,11] were used to screen drooling. The factors associated with drooling have been reported.…”
Section: Prevalence Associated Factors and Negative Impacts Of Drmentioning
confidence: 99%
“…However, results vary among studies and the conclusion remains unclear. Factors possibly associated with drooling were severity of PD [2,14], male gender [3,10], aging [6], hallucinations [11], duration of PD [13], the sum of the scores of UPDRS part II and III greater than 28 points, dysarthria, dysphagia, orthostatic hypotension, and a history of using antidepressants [12]. Drooling during PD can have negative impact for both patients and caregivers.…”
Section: Prevalence Associated Factors and Negative Impacts Of Drmentioning
confidence: 99%